Theoretical principles of conducting agrochemical certification for environmental land use - Kuzmenko, I. (Land Management, Cadastre and Land Monitoring, 2020)
Agriculture is a promising area for agricultural production, provided that the land is environmentally friendly and sustainable. The aim of sustainable land management is to optimize the activities of agricultural workers to improve the environmental, economic and social dynamics of agricultural sector development by maintaining and improving the quality of soils and consumption products. The development of environmentally friendly land use through the use of geoinformation technologies is possible due to the creation of a logical base that provides information not only about the state of land resources, but also about the main causes of deterioration in the quality of agrochemical indicators. Due to the nature and complexity of land issues, geoinformation systems in the form of information databases help to solve issues of land management and agroenvironmental zones. At the same time, this spatial stratification contributes to the involvement of farmers and local governments in the overall process of improving agriculture and environmental management. Geoinformation systems in agrochemical certification are focused on preventive maintenance, not rehabilitation, and provide methodology and approach to integrate socio-economic and biophysical information needed to improve green land use strategies. The novelty of this study is to improve the processes of information support for landowners by creating and filling the registration base of agricultural enterprises engaged in growing organic crop production. Keywords: ecological safety, landmanagement, agroecological zones, geoinformation systems.